2019
DOI: 10.1002/cplu.201900170
|View full text |Cite
|
Sign up to set email alerts
|

Pt−Co Alloy Nanoparticles on a γ‐Al2O3 Support: The Synergistic Effect between Isolated Electron‐Rich Pt and Co for Automotive Exhaust Purification

Abstract: Invited for this month's cover is the group of Dr. Katsutoshi Sato and Prof. Dr. Katsutoshi Nagaoka (Kyoto University) and collaborators at Oita and Kyushu Universities. The cover picture shows the proposed mechanism for automotive exhaust purification over a Pt–Co alloy nanoparticle catalyst with an extremely low Pt/Co molar ratio. In the catalyst, the isolated electron‐rich Pt atoms are present on the surface of the nanoparticles and play an important role in NOx capture and activation, which are important e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was suggested that the improvements in ORR activity are associated with strain effects, i.e. the changes in Pt-Pt bond distances, and the electronic effects arising from bimetallic interactions between the Pt and the Co metals [9][10][11][12][13][14]. The corresponding effects have been investigated as a function of Pt-Co alloy stoichiometry, the structure, and the composition of core-shell nanostructures supported on carbon [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the improvements in ORR activity are associated with strain effects, i.e. the changes in Pt-Pt bond distances, and the electronic effects arising from bimetallic interactions between the Pt and the Co metals [9][10][11][12][13][14]. The corresponding effects have been investigated as a function of Pt-Co alloy stoichiometry, the structure, and the composition of core-shell nanostructures supported on carbon [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%